Architectural Anthropology: Exploring Lived Space - Cedeño-Pérez, Martha Cecilia (Quaderns de l'Institut Català d'Antropologia, 2023)
Architectural Anthropology. Exploring Lived Space Stender, M., Bech-Danielson, C. y Landsverk Hagen, A. (Eds.) (2022) London: Routledge 288 p. ISBN: 9781003094142